Transcendent and Tragic Aspects of American Philosophy: Religiöse Vielfalt im amerikanischen Pragmatismus – neue Einsichten - Hein Retter (International Dialogues on Education: Past and Present, 2016)
This essay builds on Wilhelm Wundt’s thesis from 1911that American pragmatism („American philosophy“) can only be understood through its religious philosophy. When examining this claim more closely, one can discover an impressive multiplicity of religious perspectives with a modern habitus among the founding fathers of pragmatism. They generate insights worthy of consideration for contemporary societies advancing in secular processes. Some of these insights are tragic because they concern problems of our time that cannot be solved „pragmatically“.